Silicon implementation of micro pressure sensor - Yufridin, Wahab; Zayegh, Aladin; Begg, Rezaul (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/